Financing bidders in takeover contests - Vladimirov, Vladimir (Journal of Financial Economics, 2015)
This paper argues that endogenizing how acquirers finance their cash bids is just as important for understanding bidding in takeovers as endogenizing acquirers׳ payment method choice. The paper shows that acquirers finance their cash bids with equity only if they lack access to competitive financing. This leads to underbidding and lower takeover premiums. Conversely, acquirers with access to competitive financing use debt and overbid. Endogenizing the payment method reveals that security (e.g., stock) bids carry lower premiums than cash bids, backed by competitive financing. These insights find empirical support and could help explain existing evidence, which contradicts prior theory.